The World and Speech Behavior Pictures of Orthodox and Pentecost Representatives: Comparative Analysis - Kalinovskaja, Oksana (Respectus Philologicus, 2003)
The article proposes the analysis of the world and speech behaviour pictures of Orthodox and Pentecost representatives. For this aim the discourse-techniques reflecting the interdisciplinary approach are used. These techniques consist of identification-interpretive, rhetorical and genre-narrative kinds of the analysis. The texts testifying the believers' narration of their coming to the God have been taken as a material for the research.
Keywords: picture of the world; picture of speech behaviour; orthodoxy; Pentecost; genre of testifying; causal-genetic modeling; category discourse; intertextuality